Effects of Xylanase and Bacterial Inoculants on In Vitro Rumen Fermentation Pattern of Seasonal Pasture Hay and Green Maize Based Silage - Kansagara, Yash G.; Savsani, Harish H.; Chavda, Mitesh R.; Chavda, Jignesh A.; Makwana, Rinkesh B.; Karangiya, Vijay K.; Belim, Saman Y.; Makwana , Kirti R. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to evaluate the effects of xylanase and bacterial inoculants on in vitro rumen fermentation pattern of seasonal pasture hay and green maize based silage. Different silages were prepared by using green maize fodder and seasonal pasture hay in the proportion of 10:0 & 7:3 ratio in plastic jars of 3 kg capacity by adding common salt @ 0.5%, urea @ 1% and molasses @ 1.5% in each silage with seven different treatments, viz., Control (only green maize), PH (green maize and seasonal pasture hay in 7:3 ratio), X (PH added with xylanase), LP (PH added with L. plantarum), LF (PH added with L. fermentum), LPLF (PH added with both bacterial inoculants) and XLPLF (PH added with xylanase and both bacterial inoculants). Xylanase, L. plantarum and L. fermentum were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were used for in vitro study after 45 days of ensiling. None of the additives affected rumen pH. IVDMD (in vitro dry matter degradability ) was found significantly (p<0.05) higher in X, XLPLF and LPLF silages. All additives significantly (p<0.01) increased IVOMD (in vitro organic matter degradability) except LF silage as compared to PH silage. Values for total gas production and TVFA (Total volatile fatty acids) production were significantly (p<0.001) increased during in vitro rumen fermentation and that of PF (partitioning factor) were significantly (p<0.001) decreased in all additives inoculated silages as compared to PH silage. Content of NH3-N (Ammonia nitrogen) was significantly (p<0.001) higher in LP silage and that of total N was significantly (p<0.001) higher in X, LP, XLPLF silages as compared to PH silage during in vitro study. It could be concluded that xylanase and lactic acid bacterial (LAB) inoculants improved rumen fermentation quality of silage. Among all additives, xylanase is the best silage additive to improve in vitro rumen fermentation pattern.